Causes of Poor Service Delivery in Africa and Their Impact on Development - Odaro, Esohe Denise (Consilience, 2012)
Service delivery remains a pressing issue throughout Sub-Saharan Africa (SSA). Recently, the focus of government policies on meeting the Millennium Development Goals has increased attention on better provision of services. At present, however, services in Africa lag significantly behind those of other developing countries and are considerably more expensive than elsewhere (Foster & Briceno; 2010). This paper explores the factors affecting service delivery in SSA and compares public services provision to private sector service delivery, as well as the impact of both on development. The paper unfolds in three steps: After a brief review of the current condition of services, I will examine the shortlist of identified factors contributing to the current state of services and conclude with brief recommendations. I have excluded South Africa in my analysis because it is more developed than other countries in the region. This is by no means intended to be an exhaustive list of causal factors and capacity constraints allow for only partial considerations of primarily, water, and to a lesser extent, sanitation and electricity.